Effect of preputial washing on seminal characteristics and bacterial load in buck semen - SINHA, N K; GUPTA, V K (The Indian Journal of Animal Reproduction, 2003)
Semen was collected through artificial vagina from 10 Sirohi bucks 20 minutes after washing orpreputial sheath with 0.9% sterile saline solution in one week and without washing in the next week.A total of 60 ejaculates comprising 30 each for washing and without washing were used to study theseminal characteristics and bacterial load. There was no significant effect of washing of preputialsheath on reaction time and seminal characteristics like consistency, mass motility, deadspermatozoa(%) and abnormal spermatozoa. Bacterial load was significantly (p
Keywords: Preputial washing; buck semen; bacterial load